Evaluation of physical science literacy assessment instrument based on PISA 2025: a secondary school needs analysis - Safira, Ledya; Agustin Aulliyah, Uunwanah; Amara Valio, Farah; Permana Suwarna, Iwan (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2024)
Science literacy is an important competency in facing global challenges, as emphasized by international assessments such as PISA. Current physics assessment instruments used in schools are not aligned with the PISA 2025 framework, especially in measuring higher-order thinking skills. This study aims to identify gaps in the use of physics test instruments that refer to science literacy at the school level based on the PISA 2025 framework. This study uses a mixed-methods explanatory sequential design method, analyzing 923 questions: daily tests, textbooks, practice questions, 2013 curriculum teaching materials, and independent curriculum modules. The questionnaire was given to 85 students and four teachers in 4 schools, namely Jakarta and South Tangerang. The results showed that only 6.9% of the questions measured the identification of scientific information, while those measuring higher-order skills, such as analysis, were 2.9% and evaluation of evidence was 1.9%. Interestingly, 83.3% of the questions were irrelevant to the PISA science literacy criteria. This study reveals the mismatch of assessment in schools with international standards and recommends the development of contextual and PISA 2025. These findings provide an important foundation for educators and policymakers in improving the quality of science learning